Representasi Maskulinitas pada Karakter Putri Hijau dalam Iklan Marjan Edisi Ramadan Tahun 2024 - Tiara Veronica Khairunnissa; Kadek Dristiana Dwivayani; Ainun Ni’Matu Rohmah; Kezia Arum Sary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the forms of masculinity depicted in the character of Putri Hijau in the 2024 Ramadan edition of the Marjan advertisement using a qualitative descriptive approach. The theoretical focus of this research is Stuart Hall's Representation theory and Peter Lehman's concept of masculinity, which identifies four elements of masculinity: power, courage, heroism, and leadership. The analytical technique used is Roland Barthes' semiotic analysis, which consists of two stages: denotation and connotation. The results show that the character of Putri Hijau exhibits all four elements of masculinity, as seen in her actions and the properties she uses, such as clothing and swords. Furthermore, the colors used in the advertisement represent various meanings within the ad. Keywords: Representation, Masculinity, Advertisement.